Crocin as Neuroprotective Agonist in Oxidative Damage and Cognitive Dysfunction Induced by Aluminium Chloride and Colchicine in Rodents - Deepak Tomar; Mainuddin; Dhananjay Taumar; Anshika; Mayank; Prachi Jain; Khushi Goel; Amulya Jindal (Current Research in Pharmaceutical Sciences, 2023)
The main constituent of saffron, Crocus sativus L., is called Crocin (CR). Water-soluble carotenoids in CR possesses anti-inflammatory, analgesic, anti-edematous, as well as anti-oxidant properties, as well as to increase the number of microtubules in sheep brain microtubules and to have neuroprotective effects. For example, Alzheimer's disease (AD), where the harm of hippocampal as well as cortical neurons results in memory as well as cognitive impairment, as well as amyotrophic lateral sclerosis (ALS), where weakness in muscle is brought on by the degeneration of spinal, bulbar, as well as cortical motor neurons, are disorders which are characterized by the progressive and irreversible loss of neurons. In the current investigation, we evaluated CR's ability to protect neurons from the oxidative harm that Colchicine (Col) and Aluminum chloride (ALCL) induce.  GSH level, SOD, besides catalase reduced in the Col model's Col-treated group but was practically returned to normal in the group that received CR. When given CR instead of Col, the levels of MDA, acetylcholine esterase, and nitric oxide returned to nearly normal levels. However, in the Morris water maze test, CR significantly reduces the time it takes to reach the platform (escape latency time), indicating learning and cognitive improvement. Corresponding to this, in the passive avoidance test, the transfer delay time did not significantly increase in the CR-treated group but it did in the Col-treated group. Similar outcomes in the aluminium chloride model were attained. Thus, the present study comes to the conclusion that CR can be utilized to treat oxidative stress and illnesses linked to cognitive dysfunction, such as AD as well as Parkinson’s diseases shown against rodents resultantly.